Kajian Hukum terhadap Modus Tindak Pidana Pencucian Uang (TTPU) pada Kasus Rafael Alun Trisambodo - ⁠Nayla Balqis Milwanti; Nadia Zahira Eryka; Aurelya Putri Indra; Mellysa Helvira (YASIN, 2026)
The complexity of money laundering crimes originating from corruption offenses in Indonesia demonstrates the importance of strengthening legal studies on patterns of financial crime and their enforcement mechanisms, particularly in the case of Rafael Alun Trisambodo. This study aims to analyze the modus operandi of money laundering crimes and examine the application of Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes in the context of corruption offenses. This study used a qualitative approach with a normative juridical method and a case study design. Data were obtained through library research, legal documents, scientific journals, and analysis of laws and regulations related to money laundering crimes and corruption. The data were analyzed descriptively and qualitatively to understand patterns of financial crime and the effectiveness of law enforcement mechanisms. The results showed that the money laundering modus in the Rafael Alun Trisambodo case was carried out through the stages of placement, layering, and integration. The perpetrator concealed the origin of assets through the use of nominees, ownership of assets disproportionate to income, and investment transactions to obscure financial trails. This study also found that the Financial Transaction Reports and Analysis Center has a strategic role in detecting suspicious financial transactions through the follow-the-money approach. The conclusion of this study affirms that the application of anti-money laundering law requires strengthening asset-tracing mechanisms, proving suspicious financial transactions, and institutional coordination in law enforcement. These findings provide a theoretical contribution to the development of economic criminal law studies and practical implications for law enforcement officials in strengthening the effectiveness of eradicating money laundering crimes originating from corruption.